Phacoemulsification versus small incision cataract surgery (SICS): which one is a better surgical option for immature cataract in developing countries? - Singh, SK; Winter, I; Surin, L (Nepalese Journal of Ophthalmology, 2010)
Background: Several studies have shown comparable visual outcomes of SICS and phacoemulsification (Gogate et al 2007, Ruit et al 2007). Objective: To compare the safety and efficacy of different types of surgical procedures (phacoemulsification versus SICS) for cataract surgery in immature cataract. Material and methods: A prospective randomized controlled trial was carried out involving 93 and 89 patients with immature senile cataract selected for phacoemulsification and SICS respectively. Statistics: Mean values with standard deviations were calculated. P value of less than 0.05 was considered significant. Results: There was no difference between the groups in terms of gender, age and pre-operative visual acuity (p = 0.09). In phacoemulsification group (n=93) more than two thirds and in SICS group (n=89) more than three quarters of the patients had good visual outcome (6/6-6/18) on first postoperative day (p=0.065). Poor outcome (<6/60) was recorded in 6% (phacoemulsification group) and 1% (small incision cataract surgery group). Mean visual acuity was 0.43 ± 0.27 in phacoemulsification group and 0.47 ± 0.24 in SICS group. Mean surgery time was significantly shorter in SICS group (p=0.0003). Statistics: Data were computed and analyzed using the SPSS software program vs 10. The p value of < 0.05 was considered significant. Conclusion: There was no significant difference in visual outcome on first post operative day in between phacoemulsification and SICS technique. However, performing SICS was significantly faster. Small incision cataract surgery with implantation of rigid PMMA lens is a suitable surgical technique to treat immature cataract in developing countries. Keywords: phacoemulsification; small incision cataract surgery (SICS) DOI: 10.3126/nepjoph.v1i2.3682 Nep J Oph 2009;1(2):95-100